The role of the history of economic thought in modern macroeconomics - David Laidler (The University of Western Ontario, Department of Economics, 2001)
Most leading economics departments no longer teach the History of Economic Thought. Prominent macroeconomists nevertheless frequently deploy inaccurate accounts of the earlier development of ideas as rhetorical devices. These same economists have, however, also taught us that an understanding of how the economy functions helps condition the behaviour of maximising agents. The History of Economic thought documents the evolution of that understanding, so it is hard to see how economic history, which is the source of all the time series data which form the empirical basis of macroeconomics, can be interpreted without its help. Some implications of this insight are discussed and illustrated.
Keywords: 330; Makroökonomik; Dogmengeschichte; Theorie